A retrospective audit of the outcomes of the Fellow Of College Of Surgeons (FCS) (General Surgery) Final Examinations - Kahn, Miriam (Department of Surgery, 2019)
Background and aim: An audit of the Fellowship of the College of Surgeons FCS (SA) Final Examination results has not been previously performed. The purpose of this study was to review and determine any predictors of outcome. Methods: The results of the FCS (SA) Final Examinations from October 2005, to and including, October 2014, were retrieved from the College of Medicine of South Africa database. The current format of the examinations consists of: two written essay question papers, an OSCE, two clinical cases and two vivas. These were retrospectively reviewed and analyzed. Predictors of failure or success were determined. Analysis was performed using IPython for scientific computing. Assumptions for the normal distribution of numerical values were made based on the Kolmogorov-Smirnov test and quantile-quantile plots. Normally distributed variables were analyzed by parametric tests. In all other cases nonparametric tests were employed. An alpha value of 0.05 was chosen to indicate statistical significance, using a confidence level of 95%. Results: During the 10-year study period, 472 candidates attempted the examinations. A total of 388 (82,2%) candidates were successful in the written component of the examination and were subsequently invited to participate in the oral/clinical component of the examinations. 9 Overall, 296 (62,7%) of candidates passed and 176 (37,3%) failed. A total of 19 candidates achieved less than 50% for both papers, yet still managed an average of more than 45%. A total of 15 (79%) of these candidates went on to fail the examination. There were 51 candidates who were invited to the oral examinations despite an average of less than 50% in the two papers, and 34 (67%) failed the overall examination. Similarly, 126 candidates were invited having failed one of the two papers of which 81 (64.3%) ultimately failed. A total of 49 candidates failed the OSCE, 82% of these candidates failed overall. There was strong correlation between paper one and paper two (r = 0.56, p-value < 0.01), oral one and oral two (r = 0.41, p-value < 0.01) and case one and case two (r = 0.38, p-value < 0.01). Similar correlations were seen between the averages of the papers versus the orals (r = 0.52, p-value < 0.01), the papers versus the cases (r = 0.5, p-value < 0.01) and the papers versus the OSCE (r = 0.54, p-vale < 0.01). Conclusion: The written papers are the main determinant of invitation to the second part of the examination. Candidates with marginal scores in the written component had an overall failure rate of 67%. Failing one paper and passing the other, resulted in an overall failure rate 64,3%. Failing the OSCE resulted in an overall 82% failure rate. With the high failure rate of candidates with marginal scores and with the inter-examination variability of the papers, it might be prudent to revisit both the process of invitation selection and the decision to continue with the long-form for the written component.